Toll‐like Receptor 2 Is Required for Autoantibody Production and Development of Renal Disease in Pristane‐Induced Lupus. Issue 6 (30th May 2013) - Urbonaviciute, Vilma; Starke, Charlotte; Pirschel, Wiebke; Pohle, Sandy; Frey, Silke; Daniel, Christoph; Amann, Kerstin; Schett, Georg; Herrmann, Martin; Voll, Reinhard E.
<x xml:space="preserve">Abstract</x> Objective The mechanisms involved in breaking immunologic tolerance against nuclear autoantigens in systemic lupus erythematosus (SLE) are not fully understood. Our recent studies in nonautoimmune mice provided evidence of an important role of Toll‐like receptor 2 (TLR‐2) in antichromatin autoantibody induction by high mobility group box chromosomal protein 1–nucleosome complexes derived from apoptotic cells. The objective of this study was to investigate whether TLR‐2 signaling is required for the induction of autoantibodies and the development of SLE‐like disease in murine pristane‐induced lupus. Methods Lupus‐like disease in C57BL/6 and TLR‐2−/− mice was induced by pristane injection. The numbers of immune cells and serum cytokine concentrations were determined by flow cytometry. Renal disease was assessed by quantification of proteinuria, histologic analyses, and enzyme‐linked immunospot assay. Results Pristane‐injected TLR‐2−/− mice generated reduced numbers of splenic CD138+/cytoplasmic κL/λL chain–positive plasma cells and displayed diminished IgG responses against double‐stranded DNA, histones, nucleosomes, some extractable nuclear autoantigens, and cardiolipin when compared with wild‐ type controls. TLR‐2 deficiency prevented the pristane‐induced systemic release of interleukin‐6 (IL‐6) and IL‐10. The absence of TLR‐2 attenuated peritoneal recruitment of CD11c+ cells and formation of lipogranulomas. Importantly, the renal disease that developed in pristane‐treated TLR‐2−/− mice was less severe than that in control mice, as reflected by milder proteinuria, reduced glomerular deposition of IgG and complement, and decreased renal infiltration of autoantibody‐secreting cells. Conclusion TLR‐2 is required for the production of prototypical lupus autoantibodies and the development of renal disease in pristane‐induced murine lupus. Interference with TLR‐2 signaling may be a promising novel strategy for the treatment of SLE.